The Genome of the Blind Soil-Dwelling and Ancestrally Wingless Dipluran Campodea augens: A Key Reference Hexapod for Studying the Emergence of Insect Innovations. (3rd December 2019) - Manni, Mosè; Simao, Felipe A; Robertson, Hugh M; Gabaglio, Marco A; Waterhouse, Robert M; Misof, Bernhard; Niehuis, Oliver; Szucsich, Nikolaus U; Zdobnov, Evgeny M
Abstract: The dipluran two-pronged bristletail Campodea augens is a blind ancestrally wingless hexapod with the remarkable capacity to regenerate lost body appendages such as its long antennae. As sister group to Insecta (sensu stricto), Diplura are key to understanding the early evolution of hexapods and the origin and evolution of insects. Here we report the 1.2-Gb draft genome of C. augens and results from comparative genomic analyses with other arthropods. In C. augens, we uncovered the largest chemosensory gene repertoire of ionotropic receptors in the animal kingdom, a massive expansion that might compensate for the loss of vision. We found a paucity of photoreceptor genes mirroring at the genomic level the secondary loss of an ancestral external photoreceptor organ. Expansions of detoxification and carbohydrate metabolism gene families might reflect adaptations for foraging behavior, and duplicated apoptotic genes might underlie its high regenerative potential. The C. augens genome represents one of the key references for studying the emergence of genomic innovations in insects, the most diverse animal group, and opens up novel opportunities to study the under-explored biology of diplurans.